2014
DOI: 10.1074/jbc.m113.515031
|View full text |Cite
|
Sign up to set email alerts
|

Defective Chemokine Signal Integration in Leukocytes Lacking Activator of G Protein Signaling 3 (AGS3)

Abstract: Background: Roles for AGS3/Gpsm1 in the immune system are not defined. Results: Loss of AGS3 expression results in defective leukocyte chemotaxis, calcium mobilization, and ERK1/2 and Akt activation. Conclusion: AGS3 is required for efficient chemokine receptor signal integration. Significance: These studies extend the functional repertoire for AGS3 in the immune system, providing unexpected regulatory mechanisms for immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…The combined role of MyD88 and TRIF in the early induction and sustained activity of NF-κB activity TLR4 signaling (46) suggests that AGS3 may be a NF-κB target gene in macrophages. An involvement of NF-κB in the induction of AGS3 is also consistent with the increase in AGS3 noted in lymphocytes following antigen receptor crosslinking (26). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The combined role of MyD88 and TRIF in the early induction and sustained activity of NF-κB activity TLR4 signaling (46) suggests that AGS3 may be a NF-κB target gene in macrophages. An involvement of NF-κB in the induction of AGS3 is also consistent with the increase in AGS3 noted in lymphocytes following antigen receptor crosslinking (26). …”
Section: Discussionsupporting
confidence: 80%
“…The levels of AGS3 are sensitive to a variety of stimuli in the cellular environment (25, 26). Here, we showed that lipopolysaccharide (LPS) stimulation raised AGS3 and LAMP-1 expression in both THP-1 cells and mouse bone marrow derived macrophages (BMDM, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have implicated AGS3 in chemokine receptor signaling. Gpsm1 −/− mouse dendritic cells and lymphocytes exhibit suboptimal responds to chemokines in chemotaxis, calcium mobilization, and effector protein activation assays (74). Conversely, AGS3 may have a positive role in neutrophil chemotaxis.…”
Section: G-protein Regulatory Proteinsmentioning
confidence: 99%
“…Among Group II AGS family members, AGS3 exhibits the greatest functional diversity and is implicated in a wide range of system and cellular functions, including adaptive responses to addiction and craving behavior, autophagy, membrane protein trafficking, metabolism, cardiovascular function, the renal response to injury (cytoprotection), ciliary biology, cystogenesis, polycystic kidney disease, asymmetric cell divisions and immune responsiveness (Blumer and Lanier, 2014;Blumer et al, 2012Blumer et al, , 2008Branham-O'Connor et al, 2014;Robichaux et al, 2017;Vural et al, 2016Vural et al, , 2010Bowers et al, 2004;Groves et al, 2010;Kwon et al, 2012;Regner et al, 2011;Sanada and Tsai, 2005;Saadaoui et al, 2017;Chishiki et al, 2017;Choi et al, 2016;Pedram et al, 2017;Singh et al, 2014;Yeh et al, 2013). How such functional diversity is achieved is not known, but may relate to the impact of the protein on basic cellular processes in a cell-and systemtype specific manner.…”
Section: Introductionmentioning
confidence: 99%